A Holistic Evaluation of Articles on PD-1 and PD-L1 Published Between 1975 and 2017: A Bibliometric Analysis. (June 2019) - Baş, Yılmaz; Şenel, Engin
Background: Bibliometrics has been used for assessing and predicting trends in macro-health science and medical systems, especially in the field of cancer. Bibliometric and scientometric studies in the field of programmed cell death 1/programmed cell death 1 ligand 1 (PD-1/PD-L1) may guide further research in this field. Objective: To perform bibliometric analysis of articles on PD-1 and PD-L1 published in the academic literature during 1975 to 2017. Method: The bibliometric analysis was performed using the Thomson Reuters Web of Science database. Results: A total of 23 813 articles were retrieved, 73.52% of which were original articles. The United States was the leading country by total publication number (n = 10 897, 10.91%), followed by China (10.54%), and produced the most literature on PD-1/PD-L1 (164.65 articles). Among the institutions identified, Harvard University (USA) contributed the most articles on PD-1/PD-L1. Conclusions: All authors and institutions in the top 10 contributor's lists were from the developed countries. Researchers from the developing and least-developed countries should be encouraged to perform novel studies on PD-1 and PD-L1.